Atypical ventricular tachycardia and syncope with left coronary artery origin from the right coronary sinus. Issue 4 (October 1993) - Amarasena, N L; Pillai, R P; Forfar, J C
Abstract : An 18 year old man suddenly lost consciousness while jogging. The ambulance crew documented atypical ventricular tachycardia and an episode of ventricular fibrillation. Coronary angiography showed the left main coronary artery arising from the right sinus of Valsalva. Subsequent surgical coronary revascularisation was successful.